Electronics Technology as a Subject: Attitude and Performance among Marine Engineering Students - Baria, Rogelio O. (JPAIR Multidisciplinary Research, 2009)
The purpose of this study is to determine the attitude towards and performance in Electronics Technology among Marine Engineering student at John B. Lacson Foundation Maritime University-Molo, Iloilo City. The data for this descriptive research was gathered through the use of twenty-item scale, "Electronics Technology Attitude Scale" and their grades in Electronics Technology subject. The participants of the study were grouped according to high school of origin, age, program, and high school scholastic achievement. To statistically analyze the data, the means and the standard deviations was employed as descriptive statistics, and the t-test for independent sample, one "“way ANOVA, and Pearson's r as inferential statistics. The significance level was set at .05 level of significance for two-tailed tests. The results showed that, the marine engineering students had "moderately positive" attitude towards electronics technology and had "moderately low" performance in electronics technology. Significant differences existed in the students' performance in electronics technology when grouped according to program and high school scholastic achievement. Finally, positive but significant correlation existed between the students' attitude towards and performance in electronics technology.
Keywords: Electronics technology; attitude; performance; marine engineering students